On the origin of species / The Illustrated Edition - Darwin, Charles, 1809-1882.; Quammen, David, 1948- (New York : Sterling, 2008)
Reintroduces the author's work about the theory of evolution with over three hundred fifty illustrations and photographs, accompanied by excerpts from his diaries, letters, and other writings.
Includes index.
Keywords: Evolution (Biology); Natural selection